Soil-binding ability of vegetation roots in enhancing erosion resistance of a shallow slope. Issue 4 (7th August 2016) - Shahriar, Minhaz M.; Wang, Jay X.; Alam, Shaurav; Patterson, William B.
Abstract : Research was undertaken to quantify the root effect of the Johnson grass roots on the resistance increase in resisting surface erosion, in an effort to evaluate soil-binding or anti-erosion ability of the roots. In this study, an innovative means was proposed to evaluate erosion resistance of rooted soils using the traditional slope stability method. The surface erosion was treated as a special slope stability problem on the shallow slip surfaces that are parallel to the slope surface. It was assumed that factors of safety (F.S.) against these shallow slip surfaces are a direct measure of resistance to the surface erosion and the overall slope stability is not our concern. The proposed method to evaluate the surface erosion resistance of rooted soils is simple, straightforward, feasible, and easily implementable. In the research, individual roots in different zones below the slope ground were tested for their tensile strengths, and capabilities to increase shear strength of soil were assessed accordingly. Soil samples with and without roots of the grasses were collected from Ruston, Louisiana. Direct shear tests were conducted to investigate the overall increase in shear strength of the rooted soils. In the slope stability analysis, the anchor reinforcement method (ARM) was developed by considering those individual roots as independent anchor reinforcements. The erosion resistance analyses were performed by utilizing commercial software program Slope/W to evaluate the grass soil-binding capability following the smeared method (SM) and the ARM. Variations in F.S. were investigated for the specific shallow slip surfaces parallel to the slope surface for the plain soil and root-reinforced soil cases.